Association between healthy lifestyle on life course and multimorbidity in adults: results from two national prospective cohort studies - Xiaoying Ye; Mengdan Liang; Zhehui Chen; Xiannuan Jiang; Mengying Xie; Xiaowei Xie; Guohui Lan; Xiaoli Lu; Zelin Huang; Tingting Xu; Xiaoxu Xie (BMC Public Health)
Abstract Objectives To examine the correlation between healthy lifestyle patterns, their change trajectories, and the risk of multimorbidity in adults. Methods Based on two representative national cohorts, the English Longitudinal Study of Aging (ELSA) and the Health and Retirement Study (HRS) including adults aged 50 years and over. We employed Cox regression, lifestyle change trajectories, and restricted mean survival times to explore the relationship between lifestyle (assessed by SCORE2, LE’8, and HLS scores) and multimorbidity. We also conducted mediation analysis to investigate the underlying mechanisms. Results A healthy lifestyle (higher LE’8, higher HLS, or lower SCORE2) can reduce the risk of multimorbidity. 2-10% lower multimorbidity risk per one-point increase in LE’8 and HLS. The hazard ratio of multimorbidity for improvements in unhealthy lifestyles or deterioration in healthy lifestyles compared to always healthy lifestyles ranged from 1.598 to 5.602. Besides, for LE’8 and HLS, participants with higher scores had a slower decrease in survival probability in ELSA. Triglyceride, C-reaction protein, fibrinogen, and cystatin C partly mediate the association between lifestyle and multimorbidity. Conclusions Keeping a healthy lifestyle over time can help reduce the risk of multimorbidity.